The Yard and Korean Shakespeare - Lee, Hyon-u (Multicultural Shakespeare: Translation, Appropriation and Performance, 2013)
Since the New Globe Theatre opened in 1996, they have used the yard as an acting area or entrances. Even though the authenticity of using the yard is disputable, nobody denies that the yard must be a very effective tool for performing Shakespeare at the Globe Theatre. The yard is an essential part of traditional Korean theatre, called “talchum (mask dance)” or “talnori (mask play).” The yard is its stage as well as the auditorium. Therefore, the players are surrounded by the audience, and the players can, and often do interact with the audience, speaking to the audience, or treating them as players, or acting as if they were some of the audience. The theatrical style of using the yard has much influenced the modern theatre of Korea. And many Korean directors including Oh Tae-suk, Yang Jung-ung, Sohn Jin-chaek, Park Sung-hwan, and myself, have applied the yard techniques to their Shakespearean productions. Korean Shakespearean productions, which use the yard actively, can be more evidence that the yard must be an effective tool for Shakespeare, not only at the Globe Theatre but also at any kind of theatres of today. No one knows whether Shakespeare actually used the yard or not. But the fact that many Shakespearean productions have used the yard successfully, implies that Shakespeare’s texts themselves have enough room for the yard.